Implementasi Kebijakan Jaminan Ketersediaan Pangan Kota dalam Program Kartu Depok Sejahtera di Kelurahan Tanah Baru Kota Depok - Muhammad Firhan Arkananta; Abdul Rahman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Social protection programs in Indonesia play a strategic role in poverty alleviation and supporting economic development. One form of social protection implementation at the regional level is the Depok Prosperity Card (KDS) Program, implemented by the Depok City Government as a means of ensuring food security for underprivileged communities. However, the program's implementation has been deemed incompletely transparent and poorly targeted, as expressed by several members of the Depok City Council (DPRD). Therefore, this study aims to analyze the implementation of the city's food security policy through the Depok Sejahtera Card Program in Tanah Baru Village, Depok City. This study uses Charles O. Jones's policy implementation theory, which encompasses three main indicators: organization, interpretation, and implementation. The research method used is descriptive with a qualitative approach. The results indicate that, from an organizational perspective, the Depok Sejahtera Card Program has been implemented quite well, characterized by a clear division of tasks among relevant stakeholders. From an interpretive perspective, the program has a strong legal basis through Depok Mayor Regulation Number 79 of 2022 and aims to reduce poverty. However, various obstacles remain in the implementation aspect, resulting in program implementation not being optimal and efficient. Nevertheless, the program is considered beneficial for recipient communities, although an increase in the amount of assistance is still needed to meet food needs for a period of one month.